The influence of dark triad-specific personality traits (Machiavellianism, narcissism, psychopathy) on parenting styles, and parental competence in raising and educating children - Petrica, Elena; Panisoara, Georgeta (Global Journal of Social Sciences Studies, 2024)
This study aims to determine the existence of an association between the Dark Triad personality traits, parental competence, and parental styles. The parentsʼ personality traits, particularly those of the Dark Triad, may serve as predictors of the child’s level of development, educational path choices, academic outcomes, well-being, and overall development. It is of utmost importance to identify these traits to better understand the parents’ behaviour and the potential harm the parent’s strategies may inflict on the child. The Dark Triad-specific personality traits can lead to authoritarian, selfish, lacking empathy, and even manipulative behaviors that can significantly and negatively impact a child’s life. The research sample includes 609 respondents who fulfil the role of parent. The results revealed that parents’ Machiavellian personality traits may be associated with an authoritarian or permissive parenting style, but not with a democratic parenting style. Also, the level of parental competence varies depending on the background of the parents and may be influenced by their psychopathic personality traits.